Angular momentum dynamics in DMS quantum rings driven by Dresselhaus spin–orbit and s−d exchange interactions - Lia, J.M.; Tamborenea, P.I. (Physica. E, Low-dimensional systems & nanostructures, 2024)
We study the quantum dynamics of an electron subject to the Dresselhaus spin–orbit interaction (SOI) and few magnetic impurities confined in a narrow semiconductor quantum ring. The exchange interaction between the electron and the magnetic Mn impurities is modeled via a Kondo-like Hamiltonian. The role of the Dresselhaus SOI is to mediate between the orbital and spin angular momentum of the electron. Our goal is to explore and analyze in the time domain the transference of angular momentum between the electron and the system of Mn impurities. We aim to contribute to the search for mechanisms that facilitate the effective magnetization of the impurity system via the interaction with charge carriers, without the use of external magnetic fields. We pose and numerically solve the equations of motion of the reduced density matrix for our multiparticle system, resorting to a state-of-the-art truncation scheme. We first obtain the dynamics without the SOI and show how the Mn impurities strongly modify the electronic angular momentum. Secondly, we add the SOI and describe the competition that occurs between the two interaction mechanisms. In our analysis, we profit from the fact that for a one-dimensional quantum ring with only SOI the Hamiltonian reduces to block-diagonal form and the exchange interaction couples rather weakly different blocks. As general trends, we find that the SOI slows down the magnetization of the impurities and superimposes rapid oscillations in the evolution of the electron’s orbital angular momentum. •Electron and Mn impurity angular momentum dynamics in DMS QR with Dresselhaus SOI.•Case study of a (Zn,Mn)Se DMS quantum ring in the highly-diluted limit.•Time-domain numerical study employing truncated density matrices.